Impact Analysis Of Covid-19 Pandemic On E-Commerce In Indonesia Business And Recovery Strategies In The Era Of New Normal - Suwandi, Suwandi; Mege, Stacia Reviany; Werdani, Riandhita Eri; Kurniawati, Nurul Imani (Universitas Diponegoro, 2022)
The purpose of the study was to analyze the impact of the covid-19 pandemic on E-commerce business in Indonesia and recovery strategies in the era of new normal. This study uses qualitative method. Collecting data using observations, interviews and focus group discussion with research subjects including E-commerce business actors, logistics practitioners and employees in shipping services companies. The result showed that the covid-19 pandemic had an impact on E-commerce businesses. There was decline in income for 85,83% of E-commerce business actors. The decline in smoothness distribution occurred in almost all province in Indonesia.